DIGITALISASI LAPORAN TRANSAKSI KEUANGAN UMKM SEKTOR KULINER BERDASARKAN “SAK EMKM” - F.X. Kurniawan Tjakrawala; Ricky Sinaga; Louis Joshua (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The purpose of community service engagement is to provide counseling/training on aspects of financial transaction reporting in the digital ecosystem based on msme’s standard in order to increase adequate financial literacy for msme entrepreneur, especially the culinary industry sector. The owner of the Restaurant